The role of teachers in creating interest in education in primary school students in Parsian - Mashinchi, Ali Asghar; Akbari, Alireza (IJRDO- Journal of Educational Research, 2017)
The purpose of this study was to investigate the role of teachers in creating interest in educationin primary school students in Parsian. This is an applied survey one. The statistical population ofthis research includes 50 elementary school teachers in Parsian. Since the size of the communitywas small and the elements are available, sampling has not been done and all the teachers havebeen studied. The data gathering tool in this research is a researcher-made questionnaire basedon the research needs with 45 closed questions. The validity of the questionnaire was based onthe experts' perspective and their reliability was based on the Cronbach's alpha coefficient. Thereliability of the questionnaire was 0.813 which indicates the desirable reliability of the researchquestionnaire. Descriptive statistics (frequency, percentage, standard deviation and variance) andinferential statistics (one sample t test and Friedman test) were used to analyze the data. Theresults of this research indicate that teachers have a significant and meaningful role in motivatingand interesting in studying elementary school students